FM1-5 The impact of neurosurgical technique on outcome of adult patients with chiari I malformation. Issue 3 (14th February 2019) - McAllister, SM; Gallo, P
Abstract : Objectives: This study aimed to compare and evaluate any differences in clinical and radiological outcomes between three surgical techniques of cranio-cervical decompression (CCD) in adults with symptomatic Chiari malformation type I (CM1). Design: Retrospective review using the theatre management system (ORSOS) and records of the patients who underwent CCD for CM1 from January 2011 to January 2018. Subjects: Patients over 16 years of age who underwent CCD secondary to CM1 diagnosed by clinical and radiological criteria. Methods: Patients were divided in three cohorts according the operative technique used: an extradural osteo-ligamentous decompression (BD), BD plus dural opening either without duroplasty (DOWD) or with watertight augmentative duroplasty (DOPD). The primary clinical outcome was measured by utilizing the Chicago Chiari Outcome Scale (CCOS). Syrinx outcome was measured on post-op MRI. Statistical analysis was performed using IBM SPSS 24 with α=0.05. Results: Fifty-two adults underwent fifty-three CCD: 7 BD, 29 DOWD, 17 DOPD. Median follow-up was 12 months (IQR 6–23). Patients who underwent BD or DOPD had a shorter median hospital stay (6 days) than DOWD (11 days). Median CCOS was lower following DOWD (13) compared to BD (14) and DOPD (15). Post-operative complications were higher in DOWD (51.7%) compared to DOPD (17.5%). Conclusions: Better clinical outcomes, lower complication risk and shorter duration of hospital stay were associated with DOPD. Prospective randomized studies could confirm these findings.